2005
DOI: 10.1530/eje.1.01821
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adiponectin is decreased in nonalcoholic fatty liver disease

Abstract: Objectives: Nonalcoholic fatty liver disease (NAFLD) is a major cause of liver-related morbidity and is frequently associated with obesity and metabolic syndrome. The recently discovered hormone adiponectin is produced by adipose tissue, and low plasma adiponectin is considered a key factor in the development of the insulin resistance underlying metabolic syndrome. Animal studies suggest that adiponectin may protect against non-alcoholic steatohepatitis, but direct evidence in humans is lacking. We therefore c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
155
4
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(178 citation statements)
references
References 27 publications
15
155
4
2
Order By: Relevance
“…Adiponectin, although not measured in this study, has been shown to be low in NAFLD [25] and in some patients with AN [26]. The relationship between low adiponectin and NAFLD has been described in overweight patients [25], but has not been examined in AN. In addition to low adiposity, young women with AN may have hormonal or nutritional abnormalities that facilitate the development of NAFLD.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Adiponectin, although not measured in this study, has been shown to be low in NAFLD [25] and in some patients with AN [26]. The relationship between low adiponectin and NAFLD has been described in overweight patients [25], but has not been examined in AN. In addition to low adiposity, young women with AN may have hormonal or nutritional abnormalities that facilitate the development of NAFLD.…”
Section: Discussioncontrasting
confidence: 55%
“…Although speculative, patients with lower adiposity may have increased susceptibility to NAFLD due to lower levels of adiponectin, an adipocytokine that increases fatty acid oxidation and decreases inflammation [24]. Adiponectin, although not measured in this study, has been shown to be low in NAFLD [25] and in some patients with AN [26]. The relationship between low adiponectin and NAFLD has been described in overweight patients [25], but has not been examined in AN.…”
Section: Discussionmentioning
confidence: 64%
“…Adiponectin, TNF-a and leptin were not associated with the extent of hepatic fibrosis Bugianesi et al (24) 174 NAFLD patients and 42 controls Adiponectin serum levels were inversely correlated to the percentage of hepatic fat content and no association was established with necroinflammation or fibrosis Pagano et al (18) 17 NAFLD patients and 20 matched controls Plasma adiponectin was significantly lower in NAFLD patients than controls but similar in simple steatosis and in steatohepatitis Targher et al (19) 60 NAFLD patients and 60 controls. Low adiponectin levels independently predicted hepatic steatosis and necroinflammation but not fibrosis Wong et al (21) 80 NAFLD patients and 41 healthy controls Low adiponectin level and increased leptin level were associated with NAFLD.…”
mentioning
confidence: 99%
“…Patients with NAFLD have lower levels of adiponectin compared with healthy control subjects, independent of components of the metabolic syndrome [46,48,49]. This observation may be relevant because some studies have shown that lower levels of adiponectin are associated with CVD [50].…”
Section: Adiponectin Leptin and Resistinmentioning
confidence: 98%